Bone marrow mesenchymal stem cell‐derived exosomes improve renal fibrosis by reducing the polarisation of M1 and M2 macrophages through the activation of EP2 receptors - Yuqing Lu; Lulu Yang; Xiao Chen; Jing Liu; Anqi Nie; Xiaolan Chen (IET Nanobiotechnology)
Abstract Renal fibrosis is the pathological outcome of most end‐stage renal diseases, yet there are still limited therapeutic options for it. In recent years, bone marrow mesenchymal stem cell‐derived exosomes (BM‐MSCs) have received much attention. Here, we investigate the therapeutic effect of BM‐MSCs on unilateral ureteral occlusion (UUO)‐induced interstitial fibrosis in the kidney by modulating prostaglandin E2 receptor 2 (EP2). Renal pathological changes were evident in the UUO group compared to the control group, with significantly increased expression of α‐smooth muscle actin (α‐SMA), fibronectin, Ep2 and F4/80+CD86+ and F4/80+CD206+ cells in the UUO group (p< 0.05). Pathological changes were alleviated and F4/80+CD86+ and F480/+CD206+ cells were reduced after exosome or EP2 agonist intervention compared to the UUO group. These data were further confirmed in vitro. Compared to the lipopolysaccharide (LPS) group and the LPS + exosome + Ah6809 group, the lipopolysaccharide (LPS) + exosome group and the LPS + butaprost group showed a significant decrease in α‐SMA expression, a decrease in the number of F4/80+CD86+ and F4/80+CD206+ cells, a decrease in interleukin (IL)‐6 and an increase in IL‐10 levels. Therefore, we conclude that BM‐MSCs can reduce the polarization of M1 and M2 macrophages by activating EP2 receptors, thereby ameliorating renal fibrosis.